Wheat Response to NPK Nutrients and Its Economics in Punjab Province (Journal of Agriculture and Veterinary Science, 2024)
Balanced use of fertilizer is important to achieve optimum yields of wheat. Present study was conducted at farmers’ fields in Rice-Wheat and Central mixed cropping zones of Punjab Pakistan for four years from 2019-20 to 2022-23. The objectives of the study were to determine economic optimum dose of nitrogen, phosphorus and potash nutrients for obtaining optimum wheat yields under irrigated conditions. The levels of N used in this study were (0, 53, 106, 160 and 212), for P2O5 were (0, 57, 114 and 171) and for K2O were (0, 30, 60) kg ha-1 of nutrients. These levels were incorporated in 11 treatments combination according to FAO central rotatory design. All P and K were applied at sowing whereas half N was applied at sowing and remaining N was top dressed at first irrigation. Results of 56 field trials conducted in these two zones indicated that 160 and 114 kilograms of N and P2O5 respectively per hectare proved economical doses for getting highest wheat grain yield in both these cropping zones. However, for K2O, the economical doses were 30 and 60 kg ha-1 for central and rice zones respectively. The study will help revisiting the current fertilizer recommendations. More experimentation is needed to go for imparting site-specific nutrient recommendations for economical crop production.